L'urbanistica riconoscerà mai il ruolo dei sistemi informativi territoriali? - Salvemini, Mauro (GEOmedia, 2012)
It is discussed the role of GI in contemporary city  planning  considering  three  2012  May events.REAL  CORP  2012  in  Schwechat  which  of-fered  the  possibility  to  collectively  discuss a  wide  range  of  topics  in  different  panel groups  and  workshops  about  "RE-MIXING THE CITY” which is a challenge to manage and  re-combine  the  elements  which  make our modern cities in order to better respond to change. INPUT  2012  which  in  Cagliari  was  discuss-ing how new technologies play a prominent role in the innovation of planning theory and practice,  as  they  affect  every  phase  of  the process:  knowledge  building,  preliminary studies,  design,  decision,  implementation, and monitoring.The kick off of the EC co-funded project Plan-4Business which aims to develop a platform that can serve users a full catalogue of plan-ning data such as transport infrastructure, re-gional plans, urban plans and zoning plans.